Study of closing time pattern and type of valve on water hammer phenomenon in water conveyance line - Hadis Ghanbari; Jafar Mamizadeh; Majid Valizadeh (مدل‌سازی پیشرفته در مهندسی عمران)
Water hammer is a phenomenal that occures due to suddenly pump stop and closure of valve in transmission pipelines and urban water distribution network. This phenomenon is important in transmission pipelines project and ignore this phenomenon can cause a lot of damage to project implements. Several software based on numerical methods have been developed for water hammer analysis. In this research using AFT Impulse software, Hammer software and written program by characteristics method, closing time pattern and type of valve on water hammer in three sample problem is studied. The results of all three numerical models were consistent and estimate maximum pressure head with a maximum of one percent of difference. In the third sample problem that the valve closure was exponential, hammer software estimate pressure head with 12 percent lower than AFT Impulse. In other part of research, the effect of valve closure pattern on the water hammer have been investigated and the results showed that the valves were closed linearly are the most suitable valve for use in places where this phenomenon occurs.